2017
DOI: 10.1177/0884533617691250
|View full text |Cite
|
Sign up to set email alerts
|

Acquired Amino Acid Deficiencies: A Focus on Arginine and Glutamine

Abstract: Nonessential amino acids are synthesized de novo and therefore not diet dependent. In contrast, essential amino acids must be obtained through nutrition since they cannot be synthesized internally. Several nonessential amino acids may become essential under conditions of stress and catabolic states when the capacity of endogenous amino acid synthesis is exceeded. Arginine and glutamine are 2 such conditionally essential amino acids and are the focus of this review. Low arginine bioavailability plays a pivotal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
86
0
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 125 publications
(98 citation statements)
references
References 204 publications
4
86
0
3
Order By: Relevance
“…Our study showed changes in glutamine metabolism and alterations in arginine and proline metabolism (p < 0.0001, impact 0.44; Table S4). Similar to glutamate, glutamine becomes an essential AA under oxidative stress, disease conditions, or catabolic states [15] and plays a role in intestinal mucosal integrity, antioxidative responses, and immunity and cell signaling [53]. Glutamine concentrations and the glutamine to glutamate ratio in plasma are strongly inversely associated with insulin resistance.…”
Section: Discussionmentioning
confidence: 99%
“…Our study showed changes in glutamine metabolism and alterations in arginine and proline metabolism (p < 0.0001, impact 0.44; Table S4). Similar to glutamate, glutamine becomes an essential AA under oxidative stress, disease conditions, or catabolic states [15] and plays a role in intestinal mucosal integrity, antioxidative responses, and immunity and cell signaling [53]. Glutamine concentrations and the glutamine to glutamate ratio in plasma are strongly inversely associated with insulin resistance.…”
Section: Discussionmentioning
confidence: 99%
“…Patients on L-glutamine showed significant reduction in the painful crises and hospitalization (NCT01179217). The rationale behind using L-glutamine is based on the fact that sickle RBCs have low nicotinamide adenine dinucleotide (NAD) and glutamine is a precursor of NAD, hence supplementation will counter the oxidant-dependent pathophysiology of sickle RBC [5,4446]. Arginine is another anti-oxidant candidate, which has shown significant promise in the management of complications associated with SCD.…”
Section: L-glutaminementioning
confidence: 99%
“…Arginine therapy resulted in promotion in the healing of long standing refractory ulcers and significant reduction in pain episodes in SCD patients [47,48]. Furthermore, Glutamine is an arginine prodrug which may also explain some of the benefits of these types of therapies [46]. …”
Section: L-glutaminementioning
confidence: 99%
“…Glutamine, the most abundant amino acid in the body, is considered conditionally essential in the catabolic state occurring among others in critical illness, trauma, and infection [1]. Administration of high doses of glutamine in critically ill patients, however, was associated with increased mortality in a large multi-center trial [2].…”
Section: Introductionmentioning
confidence: 99%